An integrative system biology approach to delineate complex genotype-phenotype associations in Autism Spectrum Disorder - Asif, Muhammad (2018)
Objectives: To identify clinically similar subgroups of individuals with ASD [To reduce ASD heterogeneous phenotype]; To find biological processes disrupted by rare CNVs targeting brain genes in ASD subjects [To maximize the reproducibility with other data sets]; To train a machine learning classifier for the clinical prediction of disease progression from genetic information in very young children [To facilitate clinical doctors in diagnosis]